A study to determine the knowledge of pharmacovigilance among pharmacy students from Mumbai university - Limaye, Dnyanesh; Shah, Purav; Shah, Akhil; Pillay, Ragini; Modak, Viraj; Chaudhari, Ameya; Sydymanov, Arlan; Limaye, Vaidehi; Pitani, Ravi Shankar; Sathe, Sushama; Fortwengel, Gerhard (International Journal of Research in Medical Sciences, 2018)
Background: Pharmacovigilance (PV); also known as drug safety surveillance, is the science of enhancing patient care and patient safety regarding the use of medicines by collecting, monitoring, assessing, and evaluating information from healthcare providers and patients. Pharmacists are pivotal players in adverse drug event (ADE) monitoring and reporting. However, most pharmacists are unaware or not knowledgeable about the guidelines used by their respective countries’ drug regulatory bodies. It is the need of the hour to train pharmacy students on the concept of pharmacovigilance. Methods: A cross-sectional study was carried out among pharmacy students from Mumbai University, India during May-June 2017. On the basis of the eligibility criterion 352 students were selected for the present study. Four hundred students were approached to participate in the study of which 201 agreed to participate (males: 179; females: 173). Pretested questionnaire was distributed and collected data was analyzed using IBM SPSS version 23. Results: Overall pharmacovigilance knowledge (44%) and perception (58%) was low among the participants of the present study. Seventy four percent of the participants felt that adverse drug reaction (ADR) reporting should be made compulsory for healthcare professionals. And only 21% agreed that the topic of Pharmacovigilance is well covered in pharmacy curriculum. Conclusions: Pharmacy council of India, pharmacy teacher’s association and respective pharmacy college should take necessary steps to increase the knowledge and create awareness regarding pharmacovigilance and adverse drug reaction reporting among pharmacy students.